Extension of Bulevirtide monotherapy to 72 weeks in HDV patients with compensated cirrhosis: Efficacy and safety from the italian multicenter study (HEP4Di). (March 2023) - Anolli, M.P.; Degasperi, E.; D'Offizi, G.; Brunetto, M.R.; Verucchi, G.; Federico, A.; Ciancio, A.; Mangia, A.; Santantonio, T.A.; Coppola, N.; Pellicelli, A.; Loglio, A.; et al.
Abstract : Background and aim: In phase II and III trials, Bulevirtide (BLV) significantly reduced HDV-RNA and aminotransferase (ALT) levels in patients with chronic hepatitis Delta virus (HDV) infection, however, data on efficacy and safety beyond week 48 in real-world settings are limited. Methods: HDV patients with compensated cirrhosis treated with BLV 2 mg monotherapy up to 72 weeks were retrospectively evaluated in this multicenter Italian real-life study. Clinical and virological variables were collected at baseline, weeks 4, 8 and every 8 weeks thereafter. Results: 93 patients were included: median age 52 years, 52% males, liver stiffness measurement (LSM) 17.4 kPa, 55% with varices, 22% with previous ascites, 53% IFN-experienced, 97% under nucleos(t)ide (NUC) treatment. Median ALT levels were 79 U/L, albumin 3.9 g/dL, platelets 70 x 10 3 /mm 3, HDV RNA 5.2 Log IU/mL, CPT score A in all patients. A virological response (undetectable HDV RNA or ≥2 Log decline vs. baseline) was achieved by 67%, 77% and 75% of patients at weeks 24, 48 and 72, respectively, HDV RNA becoming undetectable in 10%, 16% and 38%. At the same timepoints, ALT normalization was observed in 67%, 67% and 81% of the patients while a combined response (virological + biochemical) was achieved by 45%, 56% and 63%. Besides ALT, significant on-treatment declines were also observed for AST, GGT, IgG (p<0.001 vs. baseline), while albumin values increased (p=0.02). Platelets, LSM and HBsAg levels remained unchanged. BLV was well tolerated, no patient discontinued treatment for adverse events, an asymptomatic increase in bile acids occurred in all patients. During BLV treatment, liver decompensation occurred in one patient, de-novo HCC in two, three underwent liver transplantation and one died for BLV-unrelated causes. Conclusions: Extension of BLV monotherapy to 72 weeks is safe and effective in patients with HDV-related compensated cirrhosis. Virological and clinical responses increase overtime.